Long-read assays shed new light on the transcriptome complexity of a viral pathogen. - Tombácz Dóra; Prazsák István; Csabai Zsolt; Moldován Norbert; Dénes Béla; Snyder Michael; Boldogkői Zsolt (2020)
Characterization of global transcriptomes using conventional short-read sequencing is challenging due to the insensitivity of these platforms to transcripts isoforms, multigenic RNA molecules, and transcriptional overlaps. Long-read sequencing (LRS) can overcome these limitations by reading full-length transcripts. Employment of these technologies has led to the redefinition of transcriptional complexities in reported organisms. In this study, we applied LRS platforms from Pacific Biosciences and Oxford Nanopore Technologies to profile the vaccinia virus (VACV) transcriptome. We performed cDNA and direct RNA sequencing analyses and revealed an extremely complex transcriptional landscape of this virus. In particular, VACV genes produce large numbers of transcript isoforms that vary in their start and termination sites. A significant fraction of VACV transcripts start or end within coding regions of neighbouring genes. This study provides new insights into the transcriptomic profile of this viral pathogen.